Half‐Metallic Behavior in 2D Transition Metal Dichalcogenides Nanosheets by Dual‐Native‐Defects Engineering. Issue 40 (1st September 2017) - Tong, Yun; Guo, Yuqiao; Mu, Kejun; Shan, Huan; Dai, Jun; Liu, Yi; Sun, Zhe; Zhao, Aidi; Zeng, Xiao Cheng; Wu, Changzheng; Xie, Yi
Abstract: Two‐dimensional transition metal dichalcogenides (TMDs) have been regarded as one of the best nonartificial low‐dimensional building blocks for developing spintronic nanodevices. However, the lack of spin polarization in the vicinity of the Fermi surface and local magnetic moment in pristine TMDs has greatly hampered the exploitation of magnetotransport properties. Herein, a half‐metallic structure of TMDs is successfully developed by a simple chemical defect‐engineering strategy. Dual native defects decorate titanium diselenides with the coexistence of metal‐Ti‐atom incorporation and Se‐anion defects, resulting in a high‐spin‐polarized current and local magnetic moment of 2D Ti‐based TMDs toward half‐metallic room‐temperature ferromagnetism character. Arising from spin‐polarization transport, the as‐obtained T‐TiSe1.8 nanosheets exhibit a large negative magnetoresistance phenomenon with a value of −40% (5T, 10 K), representing one of the highest negative magnetoresistance effects among TMDs. It is anticipated that this dual regulation strategy will be a powerful tool for optimizing the intrinsic physical properties of TMD systems. Abstract : A dual‐native‐defects (Ti atom self‐doping and Se defects) engineering strategy is proposed to introduce a spin polarized current and local magnetic moment into 2D nonmagnetic TiSe2, bringing half‐metallic behavior with larger negative magnetoresistance.